2007
DOI: 10.1016/j.bcp.2007.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided drug design: Conferring selectivity among neuronal nicotinic receptor and acetylcholine-binding protein subtypes

Abstract: Neuronal nicotinic receptors, encoded by nine genes of the alpha and three of the beta type of subunits, and whose gene products assemble in distinct permutations as pentameric molecules, constitute a fertile area for structure-guided drug design. Design strategies are augmented by a wide variety of peptide, alkaloid and terpenoid toxins from various marine and terrestrial species that interact with nicotinic receptors. Also, acetylcholinebinding proteins from mollusks, as structural surrogates of the receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Hence, an alternative methodology must be considered. In Cys-loop receptors, the neurotransmitter-binding pockets lie at the interface between adjacent subunits (1)(2)(3)(4)(5)(6)(7)(8)(9). One could therefore use site-specific mutagenesis and biophysical characterization of activation mechanisms in recombinant receptors to find the types of subunits that line the agonist-binding pockets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, an alternative methodology must be considered. In Cys-loop receptors, the neurotransmitter-binding pockets lie at the interface between adjacent subunits (1)(2)(3)(4)(5)(6)(7)(8)(9). One could therefore use site-specific mutagenesis and biophysical characterization of activation mechanisms in recombinant receptors to find the types of subunits that line the agonist-binding pockets.…”
Section: Discussionmentioning
confidence: 99%
“…They belong to the Cys-loop receptor superfamily of transmembrane oligomers that open an intrinsic cationic or anionic channel pore upon binding of neurotransmitters, such as ACh, serotonin, GABA, Gly, histamine, or Glu (1)(2)(3)(4)(5)(6)(7)(8)(9). GluClRs are specific targets for ivermectin (IVM), a broad-spectrum anthelmintic drug used to treat filarial diseases like onchocerciasis (river blindness) and elephantiasis (lymphatic filariasis) that afflict hundreds of millions of people worldwide (10,11).…”
mentioning
confidence: 99%
“…1 and supplemental Table S3), as well as a third mutant (mutant IV) that added Q162E, V163A, L165I, and S167G to mutant III were chosen as further intermediates to test for h␣7-nAChR selectivity. Because previous reports suggest that the ␤9 -10 linker (C-loop) plays a defined role in ligand binding and gating (21,38,39), we looked at mutant II, which lacked mutation sets 5 and 1 of the ␤9 -10 linker from mutant III. Mutant IV proved unstable in yielding consistent binding characteristics and FPLC profiles (data not shown); therefore, mutant III was chosen as a final mutant of the mutated ligand-binding domain.…”
Section: Characterization Of Ls-achbp Mutants-ls-achbp Provedmentioning
confidence: 99%
“…Several studies have shown expression of ␣7 nAChR extracellular domains (9 -11) or variants (12)(13)(14), yet none have resulted in crystal structures. Studies involving the Lymnaea stagnalis (Ls) and Aplysia californica (Ac) acetylcholine-binding proteins (AChBP) have yielded many structural analyses of the binding site for these mollusk homologues (15)(16)(17)(18)(19)(20)(21). Recently determined structures of multiple ligand complexes with the AcAChBP (18,19), along with binding and mutagenesis studies, have begun to define the structural determinants of ligand specificity (4,8).…”
mentioning
confidence: 99%
“…In situ and in vitro, their behavior resembles that expected for a high-affinity antagonist. Since cholinergic neurotransmission mediates motor activity in marine vertebrates and mammals, a large number of peptide, terpinoid, and alkaloid toxins that block the nicotinic receptors have evolved to enhance predation or protect plant and animal species from predation [23] . Purification of the receptor from Torpedo ultimately led to isolation of complementary DNAs (cDNAs) that encode each of the subunits.…”
Section: Nicotinic Receptorsmentioning
confidence: 99%